Infant feeding patterns and risks of death and hospitalization in the first half of infancy: multicentre cohort study - Rajiv Bahl; Chris Frost; Betty R. Kirkwood; Karen Edmond; Jose Martines; Nita Bhandari; Paul Arthur (Bulletin of the World Health Organization, 2005)
OBJECTIVE: To determine the association of different feeding patterns for infants (exclusive breastfeeding, predominant breastfeeding, partial breastfeeding and no breastfeeding) with mortality and hospital admissions during the first half of infancy. METHODS: This paper is based on a secondary analysis of data from a multicentre randomized controlled trial on immunization-linked vitamin A supplementation. Altogether, 9424 infants and their mothers (2919 in Ghana, 4000 in India and 2505 in Peru) were enrolled when infants were 18-42 days old in two urban slums in New Delhi, India, a periurban shanty town in Lima, Peru, and 37 villages in the Kintampo district of Ghana. Mother-infant pairs were visited at home every 4 weeks from the time the infant received the first dose of oral polio vaccine and diphtheria-pertussis-tetanus at the age of 6 weeks in Ghana and India and at the age of 10 weeks in Peru. At each visit, mothers were queried about what they had offered their infant to eat or drink during the past week. Information was also collected on hospital admissions and deaths occurring between the ages of 6 weeks and 6 months. The main outcome measures were all-cause mortality, diarrhoea-specific mortality, mortality caused by acute lower respiratory infections, and hospital admissions. FINDINGS: There was no significant difference in the risk of death between children who were exclusively breastfed and those who were predominantly breastfed (adjusted hazard ratio (HR) = 1.46; 95% confidence interval (CI) = 0.75-2.86). Non-breastfed infants had a higher risk of dying when compared with those who had been predominantly breastfed (HR = 10.5; 95% CI = 5.0-22.0; P < 0.001) as did partially breastfed infants (HR = 2.46; 95% CI = 1.44-4.18; P = 0.001). CONCLUSION: There are two major implications of these findings. First, the extremely high risks of infant mortality associated with not being breastfed need to be taken into account when informing HIV-infected mothers about options for feeding their infants. Second, our finding that the risks of death are similar for infants who are predominantly breastfed and those who are exclusively breastfed suggests that in settings where rates of predominant breastfeeding are already high, promotion efforts should focus on sustaining these high rates rather than on attempting to achieve a shift from predominant breastfeeding to exclusive breastfeeding.